Iridoid glucosides from Vitex grandifolia displayed Anti-inflammatory and Antileishmania Effects and Structure Activity Relationship - OM Bello; AB Ogbesejana; M Osibemhe (Journal of Applied Sciences and Environmental Management, 2018)
In this study, two iridoids i.e. agnuside (1) and bartioside (2) were isolated from Vitex grandifolia for the first time. These potent flavonoids were purified using fractionation and were separated by Sephadex LH 20, Silica gel 60, RP C-18 and Diaion HP-20 columns. Their structure was elucidated using FTIR, 1D and 2D NMR data, these were further evaluated for anti-inflammatory and antileishmania effects. Agnuside, isolated for the first time from V. grandifolia exhibited good activity against NF-kB assay with IC50 (ug/mL) of 8.9 while bartsioside showed an IC50 (ug/mL) of 12. Agnuside (1), an iridoid showed the highest IC50 (μg/mL) of 5.38 and corresponding IC90 (μg/mL) of 7.07 against L. donovani (intracellular amastigotes in THP1 cells). Positive standards were employed in these studies. The results allowed us to establish the relationship between the structure and the activities on the basis of the different patterns of substitution, particularly hydroxylation. This study gave credence to the view that there is a link between low incidence of some diseases and consumption of vegetables hence advantages of these vegetables are beyond nutritional gains.